2017
DOI: 10.1007/s11250-017-1343-3
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of the provision of feed and healthcare on nutrient utilization and growth performance of sheep during the early or late dry season

Abstract: An on-farm study was conducted to determine the combined effects of the provision of feed and healthcare on nutrient use and growth performance of sheep during the early or late dry season. A total of 36 smallholder sheep farmers with a flock size of ≤7 was randomly selected within each of the three administrative regions in Northern Ghana. The sheep grazed on a heterogeneous natural pasture and offered crop residues as basal diet (control) or were additionally provided with a concentrate feed plus orthodox he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The ADG values for sheep and goats in the control and treatment groups were similar to those reported by Avornyo et al (2015) for sheep and goats, and by Konlan et al (2017) for sheep in studies on feed supplementation and provision of healthcare (17.8 and 45.4 g/day for sheep under control and healthcare, respectively). The live weights of goats and sheep at 3 and 12 months in our study were lower than those and Ayantunde, 2014) and they generally have a high crude protein content, but they are high in lignin content which limits intake and digestibility.…”
Section: Body Weight Development and Growthsupporting
confidence: 80%
See 4 more Smart Citations
“…The ADG values for sheep and goats in the control and treatment groups were similar to those reported by Avornyo et al (2015) for sheep and goats, and by Konlan et al (2017) for sheep in studies on feed supplementation and provision of healthcare (17.8 and 45.4 g/day for sheep under control and healthcare, respectively). The live weights of goats and sheep at 3 and 12 months in our study were lower than those and Ayantunde, 2014) and they generally have a high crude protein content, but they are high in lignin content which limits intake and digestibility.…”
Section: Body Weight Development and Growthsupporting
confidence: 80%
“…The results on flock dynamics confirmed that the mortality rate is always high in a small ruminant flock without adequate healthcare and nutrition (Konlan et al, 2017). According to Wilson (1986), the mortality rate can be up to 30% in sheep and goat flocks in Central Mali extensive livestock systems, where healthcare is inadequate and nutrition poor, particularly in the dry season.…”
Section: Flock Structure and Dynamicsmentioning
confidence: 78%
See 3 more Smart Citations